Breaking up of prolonged sitting over three days sustains, but does not enhance, lowering of postprandial plasma glucose and insulin in overweight and obese adults - Larsen, R.; Kingwell, B.; Robinson, C.; Hammond, L.; Cerin, E.; Shaw, J.; Healy, Genevieve; Hamilton, M.; Owen, N.; Dunstan, D. (2015)
To compare the cumulative (3-day) effect of prolonged sitting on metabolic responses during a mixed meal tolerance test (MTT), with sitting that is regularly interrupted with brief bouts of light-intensity walking. Overweight/obese adults (n=19) were recruited for a randomized, 3-day, outpatient, cross-over trial involving: (1) 7-h days of uninterrupted sitting (SIT); and (2) 7-h days of sitting with light-intensity activity breaks [BREAKS; 2-min of treadmill walking (3.2 km/h) every 20 min (total: 17 breaks/day)]. On days 1 and 3, participants underwent a MTT (75 g of carbohydrate, 50 g of fat) and the incremental area under the curve (iAUC) was calculated from hourly blood samples. Generalized estimating equation (GEE) models were adjusted for gender, body mass index (BMI), energy intake, treatment order and pre-prandial values to determine effects of time, condition and time × condition. The glucose iAUC was 1.3±0.5 and 1.5±0.5 mmol·h·l−1 (mean differences ± S.E.M.) higher in SIT compared with BREAKS on days 1 and 3 respectively (condition effect: P=0.001), with no effect of time (P=0.48) or time × condition (P=0.8). The insulin iAUC was also higher on both days in SIT (day 1: ∆151±73, day 3: ∆91±73 pmol·h·l−1, P=0.01), with no effect of time (P=0.52) or time × condition (P=0.71). There was no between-treatment difference in triglycerides (triacylglycerols) iAUC. There were significant between-condition effects but no temporal change in metabolic responses to MTT, indicating that breaking up of sitting over 3 days sustains, but does not enhance, the lowering of postprandial glucose and insulin.